Namibia : Financial System Stability Assessment, including Report on the Observance of Standards and Codes on Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses key findings of the Financial System Stability Assessment for Namibia, including the Report on the Observance of Standards and Codes on Banking Supervision. The financial system of Namibia appears healthy, well-run, and resilient to plausible macroeconomic shocks. Namibia has one of the most sophisticated and highly developed financial systems in Africa. It comprises a diverse range of institutions, which are mostly private. The banking sector is mature, profitable, and well capitalized. The nonbank financial institutions sector is also well developed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet